(untitled) (Saptagandaki Journal, 2022)
This study explores the role of social media in commercial vegetable farming for rural development. A study of Bharatpur metropolitan city ward no 5 Chitwan district. The objective of the study is to explore the role of social media in commercial vegetable farming for rural development. The use of social media in commercial vegetable farming is increasing rapidly now days. Many agricultural service provider companies are giving better facilities to the farmers. Social media allows users to communicate directly with the customer’s service provider’s information sharing centers etc. Farmers are using social media to increase their produce at each stage. Rural development means as overall development such as social, economic, political and cultural of rural society. Commercial vegetable farmers have been impacted by social media in all aspects of their lives. The research design adopted in this study is exploratory as well as descriptive types. The universe of the study was commercial vegetable farmers in Ward No. 5 of Bharatpur Municipality. Out of the total number of commercial vegetable farmer households, 20 households have been sampled using the quota sampling and purposive sampling methods. The data has been collected from the Rambagh, Gulabbag, Kailashnagar, and Narayanpur areas. Each area 5 respondents has been selected for the study. The study shows that 5 % respondents were used own land and 95% respondents were used leasehold land for commercial vegetable farming. Similarly 40 % respondents were used YouTube, 35 % respondents were used Facebook and 25% respondents were used Tik Tok for agriculture information. In the study area, social media seem to have a positive effect on commercial vegetable farming. Commercial vegetable farming support to livelihood, capacity building, empowerment, increase in living standard, saving habit, access to financial institutions, agricultural inputs services and market in the study area. Commercial vegetable farming has been playing a significant role for rural development in this area.